Perundungan dalam Kardiologi: Bagaimana Bersikap sebagai Kardiolog yang Beretika - Laksono, Sidhi (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
The foundation of decision-making in the health care system is patient care and results. For patient care delivery to be successful overall, staff members must be courteous, cooperative, and respectful of one another. The delivery of healthcare is positively impacted by cohesive health care teams and efficient communication. However, encounters in the health care industry are not always courteous. Among 5,931 cardiologists (77% male; 23% female), 44% reported a hostile work culture, and 79% of those who worked in a hostile work environment reported negative impacts on professional activities with coworkers and patients. These findings are supported by the Global Prevalence and Impact of Hostility, Discrimination, and Harassment in the Cardiology Workplace survey.